ACTIVATING A DIRECTED MOTIVATIONAL CURRENT THROUGH A GAMIFIED EXTRACURRICULAR ACTIVITY IN HIGHER EDUCATION: A PILOT STUDY - Amel M. Shoaib (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
The study examines the occurrence of a Directed Motivational Current (DMC) in a task-based gamified extracurricular activity in a Saudi Arabian university. An explanatory longitudinal approach was administered to detect changes to the motivational disposition and engagement of twenty-eight English majors throughout a three-week period. The study utilized multiple data sources including pre/post questionnaires, focus groups, individual virtual interviews, and BlackBoard Ultra analytics. The results of the pilot study indicate that when a gamified activity outside a program’s curricula is DMC induced, it can enhance the sense of belonging, encourage engagement, increase eudaimonistic sensations, develop linguistic and non-linguistic skills, and lead to personal benefits beyond the game, especially creativity and confidence. These activities encourage personalized and self-directed learning through entertainment, and therefore can improve the overall educational experience for students. Keywords: Directed Motivational Current, Explanatory Longitudinal Approach, Gamified Extracurricular Activity, Saudi Arabia